Ectocarpus siliculosus (Dillwyn) Lyngbye (Phaeophyceae, Ectocarpales) in the waters of the southwestern coast of the Polish part of Baltic Sea - Kowalski, Wojciech W. A. (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2025)
This paper presents information on the occurrence of the taxon Ectocarpus siliculosus (Dillwyn) Lyngbye in the coastal waters of the Pomeranian Bay. The study was conducted on two sections of the coastal zone. Material was collected point-by-point at four sites in the coastal accumulation zone, collecting floating thalli brought by sea waves. Shoots of other plants washed ashore were also collected. No thalli of other brown or red algae were found in this zone, except for the abundant green algae of the genera Ulva sp. div. and Cladophora sp. div. growing on the stones. In the second section of the coastal zone, plant material was collected at reference sites located along a designated transect. Based on the collected samples, it was found that filamentous thalli of Ectocarpus siliculosus, despite favourable local conditions for their development and the presence of stable substrate structures, appear very rarely. Thalli brought by currents and waves from other parts of the sea were observed more frequently. In the collected samples, vegetative stages were observed more frequently than sporophyte thalli with developed sporangia.